Extent of Commitment to Religious Tolerance and Acceptance of Others in Islamic Shariah and Omani Law: A Comparative Study with International Charters - Mohamed Bendari (Journal of Islamic Thought and Civilization, 2026)
Freedom of belief and the acceptance of others are issues that attract widespread attention locally and internationally, as well as from civil society. What is the position of Islam on freedom of belief and the acceptance of others? Taking Oman as a model of Islamic countries, to what extent does the Omani law align with the human right to freedom of religion? What is the stance of Islam and Omani law on apostasy and blasphemy? The evidence and texts related were clarified, analyzed, and compared with international charters. The study concluded that Omani law places a high value on freedom of belief and makes it a constitutional principle, imposing a criminal penalty for its violation. Religious tolerance reached its peak in Oman with the establishment of places of worship for all religious beliefs, including Hinduism. Additionally, Islamic law, since the time of the Prophet Muhammad (PBUH), has recognized freedom of belief and the practice of rituals to the extent that Christians were allowed to perform their rituals in a mosque. Therefore, Omani laws and Islamic laws adhere to international standards on freedom of belief and do not impose a penalty for apostasy. The study recommended amending Omani law to make the penalty for blasphemy including all religions and all places of worship, not just the Abrahamic religions and their respective places of worship.